Plan de negocio para la producción y comercialización de panela pulverizada para la finca el Mirador en el municipio de Ortega Tolima (2024)
The panela is a recognized product in several regions of the country, where the majority of low-income farmers produce this beautiful product, where the process of elaboration and production of panela is very dedicated by these beautiful people, and passed generation after generation without losing its touch. Today with globalization and automation has changed many things with respect to agricultural products always looking for innovation of these, in this case the panela block is the best known and marketed nationally and internationally.